A Feasibility Study of Urban Underground Logistics System -- A Case Study of Shanghai. Issue 1 (March 2021) - Lu, B; Zhang, M X; Fan, Y Q
Abstract: With rapid development of e-commerce, new retail and other new Internet business models, the requirements of the higher package handling efficiency and lower delivery cost are put forward in logistics industry. However, due to the lack of logistics facilities, the limitation of ground roads and the land use, the service of express delivery cannot satisfy the logistics demand, which makes the express delivery a "bottleneck" that restricts the development of urban logistics. Underground Logistics System (ULS) can be a new way to handle it. ULS refers to a logistics system which uses specific vehicles to realize the seamless connection of automatic loading, unloading, transportation, sorting and delivery of goods in the underground based on information technology. Firstly, we have studied ULS and explored its system architecture and advantages. Then, we have combined it with Shanghai Master Plan 2017-2035 and its express facilities planning, and provided a forecast of the express delivery demands in Shanghai in 2035. Based on the findings, we have proven the necessity of ULS corridors in the city. It is likely that the increase of logistics demand will bring about some urban problems such as traffic congestion, environmental pollution and resource waste, if no timely action is taken. As a new mode of urban express delivery, ULS can reduce the above negative effects and promote the sustainable development of the city.